Ethnic Signs in the 21stcentury’s fashion: Pre-Columbian Cultural manifestations in creation of atemporal products (ModaPalavra e-periódico, 2016)
The culture is manifested through knowledge, beliefs, legends, customs and ways of life of a people, which can be moved and re-interpreted in a fashion product that is hoped to be observed by an interpreter loaded with cultural background. The formal innovation is reactivated in fashion every moment with more aberrant and arbitrary forms, on the aesthetic level, with the sole purpose of providing an ever-new material of different signs. By portraying cultural aspects in fashion whether in clothing or accessories, it’s ephemerality character is reduced, since more timeless objects or products are proposed. This article aims seeks a review of the relevance of cultural events and ethnic groups in the fashion of the century, in addition to making an approach to the creative process of a collection of accessories with references in pre-Columbian cultures of the people Incas, Mayas and Aztecs.
Keywords: fashion; pre-Columbian culture; ethnic signs